2022
DOI: 10.3389/fbuil.2022.1047335
|View full text |Cite
|
Sign up to set email alerts
|

Social impact of green roofs

Abstract: Green roofs are recognised as contributing towards building-related energy efficiency. Since roofs account for 20–25% of all urban surface areas, it is not surprising that such a green system can offer a sustainable solution to decreased energy consumption. The current literature on green roofs mostly focuses on the eco-benefits of such structures. A handful of research papers1 have theorised that as green roofs become more prevalent, there will be associated social outcomes for an urban community. However, em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…That is, students were more likely to perceive the social benefits as greater, while those with more knowledge of the green roof rated the environmental benefits more highly. Students may perceive the social impact more positively than non-students because they were more likely to use the roof for social purposes [9], invoking notions of socialisation and peer interaction. While it is intriguing that those with knowledge of the green roof did not perceive both the environmental and social impacts of the green roof as greater than those with less knowledge, this could be for a few reasons.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…That is, students were more likely to perceive the social benefits as greater, while those with more knowledge of the green roof rated the environmental benefits more highly. Students may perceive the social impact more positively than non-students because they were more likely to use the roof for social purposes [9], invoking notions of socialisation and peer interaction. While it is intriguing that those with knowledge of the green roof did not perceive both the environmental and social impacts of the green roof as greater than those with less knowledge, this could be for a few reasons.…”
Section: Discussionmentioning
confidence: 99%
“…First, as the narrative around the green roof promoted by the university predominantly focused on its environmental features and performance [23], those who have knowledge of this narrative may then be more focused on the roof's contribution to the environmental SDGs rather than social. Second, as the majority of the sample used the space for social purposes [9], more people may have been aware of the possible social impacts than environmental, thus reducing the role of knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous focus group discussions had found that about 25% of participants had an incorrect or alternate definitions or ideas of a GR. Further, most recent literature using a contingent valuation survey found that 84% of the respondents visited the GR under study but only 40% were aware it was a GR (Nguyen et al 2022). To address the issue of participants potentially having a misunderstanding of what a GR is, we considered it important to provide information on GRs to ensure that respondents had a consistent understanding of them.…”
Section: Methodsmentioning
confidence: 99%
“…Professionals and decision-makers need quantitative results to prove the expected effects of GR to the public [20,[27][28][29]. Also, due to the emphasis on social sustainability, more and more GR are designed to be accessible to the public [30][31][32]. However, most existing literature and research only analyses the benefits of inaccessible GR.…”
Section: Introductionmentioning
confidence: 99%